2008
DOI: 10.1007/s10096-007-0446-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between past Chlamydia pneumoniae infection and markers of chronic inflammation in obese women

Abstract: It has been widely accepted that obesity is associated with chronic, low-grade inflammation that affects the adipose tissue as well as the entire system. The aim of this study was to assess whether past Chlamydia pneumoniae infection influences obesity phenotypes and serum levels of low-grade inflammation markers in obese, healthy premenopausal women. The study was performed on 48 obese and 42 normal-weight women, aged 31.2 +/- 7.2 years. Serum levels of C-reactive protein (CRP), tumor necrosis factor alpha (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…Before our researches, only two other studies have reported similar association. Fernaendez-Real et al 35 showed among apparently healthy men from Spain a positive relationship between total pathogen burden based on Herpes simplex virus 1 and 2, enteroviruses and C. pneumoniae IgG serostatus and fat mass and percentage of fat mass, whereas Koziolek et al 36 observed a higher prevalence of asymptomatic past C. pneumoniae infection among premenopausal obese women with body mass and percentage of body fat above median values. Despite the fact that a positive relationship between C. pneumoniae infection and elevated BMI has been reported by several authors, there are still unanswered questions of whether excessive body weight is a factor that may predispose to C. pneumoniae infection or whether C. pneumoniae infection leads to the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Before our researches, only two other studies have reported similar association. Fernaendez-Real et al 35 showed among apparently healthy men from Spain a positive relationship between total pathogen burden based on Herpes simplex virus 1 and 2, enteroviruses and C. pneumoniae IgG serostatus and fat mass and percentage of fat mass, whereas Koziolek et al 36 observed a higher prevalence of asymptomatic past C. pneumoniae infection among premenopausal obese women with body mass and percentage of body fat above median values. Despite the fact that a positive relationship between C. pneumoniae infection and elevated BMI has been reported by several authors, there are still unanswered questions of whether excessive body weight is a factor that may predispose to C. pneumoniae infection or whether C. pneumoniae infection leads to the development of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8]10,12 However, several other studies did not find such association. [27][28][29][30][31][32] Our study included over 5000 individuals, which is to the best of our knowledge, the largest study of the topic. In addition, our study population is general population based and the subjects were relatively young, 31 years of age at the time of data collection.…”
Section: Discussionmentioning
confidence: 99%
“…As most of the studies, we also used a single measurement of C. pneumoniae IgG as a marker of infection. 5,6,8,9,11,12,[27][28][29][30][31] A single IgG positive serum sample may indicate recent, past or persistent infection. 44 The simultaneous presence of elevated hsCRP with C. pneumoniae antibodies may, however, indicate that the infectious agent is currently present, possibly in a persistent form and maintains low-grade inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, it was reported that Chlamydia pneumoniae infection is associated with human obesity (17). People with persistent C. pneumoniae antibodies have a significantly higher BMI and chronic inflammation (18). This shows that bacterial infection is related to BMI in humans.…”
Section: Chlamydia Pneumoniaementioning
confidence: 99%